Implementation of Fundamental Analytical Dashboard and Stock Price Forecasting of ADRO, ANTM, INCO with Arima Approach - Najib, Marhawati; Nur Aulia Cahyani; Syamsu Alam (SAGA: Journal of Technology and Information System, 2024)
This study aims to compare the financial performance of ADRO, ANTM, and INCO and project the stock prices using fundamental analysis and the ARIMA approach. The background of this study is based on the phenomenon of herding behavior and overconfidence of investors who often ignore fundamental analysis in making investment decisions. This study adopts a quantitative method using financial ratio data and historical stock prices and a qualitative method through visualization in the form of an analytical dashboard. The results of the study show that ADRO has an advantage in terms of profitability, INCO stands out in liquidity, and ANTM experiences fluctuations in financial performance. The ARIMA model can project the stock prices of the three companies by showing a positive trend for INCO and ANTM, while ADRO tends to be stable. The analytical dashboard developed helps investors understand financial performance and stock price projections, thus supporting more accurate investment decision-making.